1995
DOI: 10.1079/bjn19950144
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and endogenous excretion of phosphorus in growing broiler chicks, as influenced by calcium and phosphorus ratios in feed

Abstract: Absorption and endogenous excretion of P by male broiler chicks (14-29 d old) were quantitatively evaluated at different Ca : P ratios (1,l: 1 ; 2, 1.5 : 1 ; 3,2 : 1 ; 4,25 : 1) in four groups given experimental diets ad lib. The P content was the same in all diets. An isotope-dilution technique was used to determine endogenous faecal and renal excretion. Ca and P retentions in the whole body were estimated according to the comparative slaughter technique. P absorption was calculated from retention and endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…This could be due to a higher accumulation of phosphorus, as hydroxyapatite, in the skeletal structure compared with the accumulation in the muscle tissue (Al-Masri et al 1995) as also confirmed by the significantly (P < 0.001) higher value of the final body weight (52 days) of the animals of the N group.…”
Section: Nutritional Characteristics Of the Meatmentioning
confidence: 50%
“…This could be due to a higher accumulation of phosphorus, as hydroxyapatite, in the skeletal structure compared with the accumulation in the muscle tissue (Al-Masri et al 1995) as also confirmed by the significantly (P < 0.001) higher value of the final body weight (52 days) of the animals of the N group.…”
Section: Nutritional Characteristics Of the Meatmentioning
confidence: 50%
“…Growth improvement by lowering the Ca to NPP ratio results from the increase in phytase activity, P digestibility, and P retention in broiler chickens (Qian et al, 1997), turkeys (Qian et al, 1996), and pigs (Liu et al, 1998;Stein et al, 2011). Lowering the dietary Ca to NPP ratio also increases the absorbed and retained P (Al-Masri, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, fewer studies have considered dietary calcium level and Ca:P ratio in phosphorus absorption relating transporter in the intestine. Increasing Ca concentration in chick diets had a large effect on P absorption (Al-Masri, 1995). Whereas, a study in pigs indicated that sodium-dependent phosphate uptake in the jejunum stimulated by a low-phosphorus diet was independent of dietary calcium concentration (Saddoris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%